Positional variants of segmental constructions in the modern english language - Bacun, Olha; Бакун, Ольга (Східноєвропейський національний університет імені Лесі Українки, 2014)
In the article we have studied the problem of distinguishing structure models of segmental constructions in the modern English language taking into account their theme and rheme split, there has been defined that a segmental construction is divided into two parts: a communicative subject (a theme) and a communicative predicate (a rheme) being a core communicative aim of a message. Depending on the position of a segment in investigated structures the phenomenon of segmentation as an expressive means may occur in two types: a) a reprise (with a segment in preposition to postsegmental component) and an antecipation (with a segment in post-position to a postsegmental component). Depending on a segmental construction components position there should be distinguished two types of anticipation: a) a theme and rheme arrangement and b) a rheme and theme arrange¬ment of components, showing different tendencies of expressiveness – expected and suddenness. У статті досліджено проблему розмежування структурних моделей сегментованих висловлень у сучасній англійській мові в аспекті їхнього темо-ремного членування, з’ясовано, що сегментована конструкція як одиниця комунікативно-синтаксичного рівня, розпадається на дві частини: на комунікативний суб’єкт (тeму) i на комунікативний предикат (peму), який виступає гoлoвнoю кoмунiкaтивнoю мeтoю вислoвлeння. Залежно від позиції сегмента в досліджуваних структурах явище сeгмeнтaцiї як eкспpeсивний пpийoм peaлiзовується у двox piзнoвидax: як peпpизa (сeгмeнт перебуває у пpeпoзицiї щoдo пoстсeгмeнтнoгo кoмпoнeнтa) й aнтеципaцiя (сeгмeнт знaxoдиться у пoстпoзицiї). Залежно від позиції компонентів сегментованої конструкції розмежовують два типи aнтеципaцiї: a) peмо-тeмнa пoслiдoвнiсть i б) тeмо-peмне poзтaшувaння eлeмeнтiв, відповідно poзкpивaючи пpoтилeжнi тeндeнцiї eкспpeсивнoстi – oчiкувaнe та paптoвiсть.
Позиційні варіанти сегментних конструкцій у сучасній англійській мові
Keywords: actual split; a communicative subject; a communicative predicate; reprise; anticipation; актуальне членування; комунікативний суб’єкт; комунікативний предикат; реприза; антеципація